Male RPAS Integration into European Airspace : Part 2: Real-Time Simulation Analysis of Operations with Remain Well Clear - Sunil, E.; Theunissen, E.; Bleakley, T.; Hartlieb, E.S.; Kuiper, P.J.; Suijkerbuijk, H.C.H.; Dufourmont, T.A.J.; Grebe, T. (IEEE, 2022)
At present, Medium Altitude Long Endurance (MALE) Remotely Piloted Aircraft Systems (RPAS) are only permitted to fly in segregated airspace in Europe. Because such restrictions limit the efficiency of MALE RPAS operations, several European projects are working on the procedures needed to allow routine MALE RPAS flights in unsegregated European airspace. To contribute to these efforts, the Royal Netherlands Aerospace Center (NLR) has partnered with General Atomics Aeronautical Systems Inc. (GA-ASI) and Information System Delft (ISD) to gather the data needed to develop MALE RPAS airspace integration procedures through a series of Real-Time Simulation (RTS) experiments. This paper summarizes the results of the second RTS campaign performed in November 2020 under this collaboration, which focused on the procedures needed for the Remain Well Clear (RWC) component of Detect and Avoid (DAA). RWC systems provide RPAS pilots with cues that reduce the chance of a Collision Avoidance (CA) situation from occurring. In this work, the GA-ASI Conflict Prediction and Display System (CPDS), a DAA alerting, guidance and display system that meets the requirements set in RTCA DO-365B, was used. In addition to an active Royal Netherlands Airforce RPAS pilot, the RTS also involved a number of experienced Air Traffic Controllers (ATCOs) and airline pilots. The experiment considered several challenging RWC scenarios in both controlled and uncontrolled airspace classes, in both en-route and Terminal Maneuvering Area (TMA) settings. This included RWC encounters during the final approach phase to analyze the procedures needed for the new DAA Terminal Alerting (DTA) logic described in RTCA DO-365B. The results indicated that both ATCOs and RPAS pilots can become accustomed to operations with RWC/DAA with relatively little additional training. The results also suggest that RPAS pilots should avoid excessive RWC-related radio communications as this could have a negative effect on ATCO workload. To this end, RPAS pilots are recommended to integrate the information provided on the DAA display with information in radio communications to determine if the ATCO is already aware of, and is in the process of resolving a conflict, before reporting it. At the same time, the procedures should provide RPAS pilots with more flexibility than described in the current standards to resolve conflicts. In TMAs, this approach is likely to reduce the number of unnecessary go-arounds needed to resolve conflicts during final approach when DTA alerts are issued.